Pengaruh Metode Bercerita Kisah Nabi terhadap Perkembangan Akhlak Anak Usia 5-6 Tahun di RA Hj. Fauziah Binjai Timur - Yani, Seri Indah; Basri, Muhammad; Al-Farabi, Mohammad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to determine the influence of storytelling about the Prophet's stories on the moral development of children aged 5-6 years at RA Hj. Fauziah Binjai Timur. The research method used is quantitative, employing a Quasi-Experimental Design with a Non-Equivalent Control Group Design type, involving a total population of 30 children from two classes, namely the experimental class (Safah) and the control class (Marwah). The selected sample for the study consists of 15 children from the experimental class who were taught using storytelling methods in their learning activities. Data collection techniques include observation sheets, test techniques (learning outcomes), pre-tests, post-tests, and documentation. The data analysis technique used includes descriptive statistical data analysis, inferential analysis, normality tests, homogeneity tests, and hypothesis tests. The research results indicate an influence on the moral development of children in the Safah class at RA Hj. Fauziah Binjai Timur. This can be seen from the post-test normality test value of 0.100>0.05, the post-test homogeneity test value of 0.392>0.05, and the significance value (2-tailed) <0.05. Therefore, it can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, indicating an influence of the storytelling method on the moral development of children at RA Hj. Fauziah Binjai Timur.